Almost-certain malignant hyperthermia during cardiopulmonary bypass: a case report and literature review. (September 2019) - Zhang, Yan; Zhou, Ronghua
Malignant hyperthermia is a well-known but potentially lethal disorder which is triggered by volatile anesthetics and depolarizing muscle relaxants. Early diagnosis and treatment could save lives. However, during cardiac surgery, hypothermia and cardiopulmonary bypass make the diagnosis of malignant hyperthermia extremely difficult than other surgeries. We report a case of almost-certain malignant hyperthermia, according to the clinical grading scale, in a patient undergoing on-pump coronary artery bypass grafting surgery. The patient underwent difficult weaning from cardiopulmonary bypass until intra-aortic balloon pump and temporary cardiac pacemaker had been implanted. Although dantrolene and corresponding treatments were administered recently, the patient died 12 days after surgery because of acute kidney failure and cardiac arrest. Therefore, it is important for us to previously recognize some specific signs of malignant hyperthermia during cardiopulmonary bypass to avoid severe outcomes.